Environmental friendly poly (vinyl) alcohol/kenaf fiber composites for agricultural applications / Tan Boon Khoon - Tan, Boon Khoon (2015)
In this study, poly(vinyl alcohol)/kenaf fibre (PVA/KF) based composites were prepared by casting from a mixture of kenaf fibre and aqueous solution of PVA. Certain amounts of urea could be loaded into the composite. The water solubility, release behaviour of urea and thermal stability of PVA/kenaf fibre/urea composites were evaluated. In a wet environment, urea was released from the composites through its dissolution in water. Around 57% of the urea was released from the PVA/KF composites in 24 hours. The composites also lost 25% of their weight after 7 days in water. Controlled amounts of methylene diphenyl diisocyanate (MDI) were added to introduce some crosslinking reactions between the diisocynante and the –OH groups of the PVA and the fibre to improve the water barrier property of the composites for prolonged water submersion. Laboratory tests were performed on cross-linked and uncross-linked PVA/KF composites to examine the effect of MDI on the properties of the composites. Water-absorption test, morphological analysis, thermal-stability evaluation, and FTIR study were performed. This cross-linked structure was able to slow down the penetration of water and enhance water resistance, as confirmed by the water-absorption test and micrographs. Thermogravimetry analysis data revealed that cross-linking improved the thermal stability of the composites. The degradation of cross-linked and uncross-linked PVA/KF composites in soil was also investigated, where sample pieces of dimension of 20 x 20 x 1 mm were buried 5 cm deep under soil in flower pots. The evidence of degradation could be seen from FTIR spectroscopy. In addition, cracks and fungal growth on the surface of the materials could be clearly observed under the microscope. The rate of degradation could be monitored from the weight loss of the sample, which increased significantly when in wet environment. The observed weight loss of PVA/KF composite was 18% in 7 days and 50% after 28 days, while MDI cross-linked PVA/KF composite exhibited a slower weight loss of 7% in 7 days to 14% after 28 days. The composites were tested in real life conditions by using them as biodegradable mulches for long bean plants in a small garden plot. The degradation of mulches and the plant growth were carefully observed. Their performance was also compared with the plastic mulch using black polyethylene films available in the market. It was found that the biodegradable mulches were able to protect the seedlings of long beans from moisture loss. As the plants have grown stronger within 30 days, the mulches have biodegraded completely, releasing the fibres as fertilizer to the soil without leaving any undegradable waste for disposal. Hence, they would not pose any risks to the land or biological systems. The composites could have great potential agricultural applications.